Sonografické vyšetření lokte - Mezian, K; Novotný, T; Chomiak, J; Hrazdira, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2021)
This introduction to ultrasound evaluation of the elbow describes the basic scanning planes and contains corresponding high-resolution ultrasound images. The patient and probe positionings are explained in a simplified step-by-step manner using schematic drawings. This standard and simple examination technique seems to be an appropriate way to improve the learning curve of novice musculoskeletal sonographers. In this manuscript, an emphasis is placed on effusion detection, ulnar nerve imaging, and commonly injured tendons assessment. This article also describes some common pitfalls to avoid when starting with musculoskeletal ultrasonography (e.g. positioning issues, unsolicited artifacts). Key words: tendons, elbow tendinopathy, golfer's elbow, tennis elbow, musculoskeletal, protocol, ultrasound, common extensor tendon, common flexor tendon, ulnar nerve.
Keywords: šlachy; Elbow; Elbow Joint; Ultrasonography; ultrasonografie; loketní kloub; Humans; loket; lidé; Tendons